A novel route for the synthesis of CNTs/WC composite powders from melamine and metal oxides. Issue 3 (15th February 2019) - Zhao, Shuning; Xiang, Daoping
Abstract: In this paper, a rapid method for preparing CNTs/ceramic composite powders is reported. Taking the CNTs/WC composite powders as an example, microwave-assisted heating on mixed powders of WO3, Co3 O4 and C3 N3 (NH2 )3 was used for the carbothermal reduction reaction in the atmospheric environment. X-ray diffraction results showed that WC powders could be prepared without any impurities by carrying out the abovementioned method at 900 °C for 10 min. The SEM images showed that a large number of CNTs were generated in all the samples and mixed evenly with the WC particles in the powder. The TEM images showed that the CNTs had an intact structure and a small number of WC particles lay on the surface. In this study, costs were reduced considerably by using cheap metal oxides as the raw materials and synthesizing without a vacuum or an inert atmosphere. Moreover, this method could solve the problem of CNTs agglomeration and realize the uniform dispersion of CNTs in powders, which is of considerable importance in the further application of CNTs/ceramic composite powders.